An Investigation on Five Year Old Preschool Children’s Art Criticism Towards Original Art pieces - Kargı, Eda (inSciencePress, 2014)
[Abstract Not Available]
The file in this item is the publisher version (published version) of the article.
Keywords: Preschool Education; Children's Art Criticism; Child and Art